Fa’atsiru Faqlidu Rokat Tase ‘ala ‘aqidatu as-shiyadin - Farhah Farhah; Nada Haninah Saifurrahman* (Journal of Comparative Study of Religions)
Rokat Tase’ is a tradition or ancestral heritage that is still preserved by coastal communities, especially fishermen. In its implementation, several rituals have become their beliefs which have a major influence on the faith of the local community. One of the rituals in this tradition is Larung Sesaji. This ritual is also one of the relics of the teachings of Hinduism, which is still preserved by the ancestors to date, leaving an impact on the fishermen. This article will discuss the implementation of Rokat Tase ‘in Pakandangan Barat village, Sumenep Madura and its influence on fishermen. Rituals in Rokat Tase’ begin with khatam al-Quran and continue with istighasah, tahlilan, Larung Sesaji that are paraded to the sea in a boat. The a Sesajen were dissolved in the form of food and goods placed in a small boat called Bithek. This ritual is not following the teachings of Islam. Besides that, there is also an art performance and ends with tabligh akbar. Rokat Tase’s implementation affects the faith of the fishermen in Pakandangan Barat village, Sumenep, Madura.